Mandatory CSR law in Indonesia; new emerging policy - Sabela (2013)
The changing CSR policy in Indonesia has yet to bring significantly social prosperity to its main beneficiaries.Article 74 of the Limited Company Liability Act has been passed since 6 years ago but unfortunately the provision is not well implemented until now.A lot of sectoral acts were related to the mandatory CSR provision.Some of the Acts are Environmental Management and Protection Act, Coal and Mineral Mining Act, Forestry Act, State Owned Company Act and Social Prosperity Act.Interconnected acts make the situation become worse because there are a lot of “players” on mandatory CSR itself.The aim of this papers is to examine mandatory CSR law in Indonesia (new emerging policy).This a concept paper to elaborate CSR implementation strategy framework from traditional to more responsive one. Not surprisingly if the provision cannot be well implemented, even though the government regulation has passed the Act in April, 2012 but there are some problems with its implementation and and detail mechanism of implementation is required for the fulfilment of mandatory CSR provision.Theory of legal system will be the tool of analysis in order to describe any constraint in the term of implementation.There are three key elements of the theory such as legal substance, legal structure and legal culture.Those elements would be analysed scientifically against related laws and regulations both national and sub-national level and law is as a tool of social engineering will be also additional tool of analysis for the research.Mandatory CSR is a concept in which it comes from the perspective of beneficiaries because in some cases corporations are more powerful than the country itself.In other words we can say that Mandatory CSR is a concept of Eastern society.Furthermore, in western society, they recognized CSR as a voluntary action.It can be well implemented there because their level of compliance to the law and other regulations are better than others society.The lives of human being is just like a cyclus of life, different age and place has different way of life or culture.Finally, mandatory CSR as an emerging policy will appear to be solution of new relationship standard between the government, corporation and society.